The impact of sugar projects on the community of White Nile State - Sudan - Ahmed, Mohamed Abdalla Mohamed (Journal of Economic, Administrative and Legal Sciences, 2025)
The paper aimed to know the impact of sugar projects on the community of White Nile State – Sudan, and its role in achieving political, economic and social stability for urban and rural communities.  The paper used several approaches, including the historical, descriptive, analytical and statistical approaches, to extrapolate reality.  The paper also used a questionnaire to measure the impact of  economic and social of sugar projects in the state.  The paper reached a number of results, the most important of which is that the establishment of development projects in the mandate of (sugar projects) helped in the stability of the local communities surrounding these projects through the implementation of programs for social and service development.  The paper concluded with several recommendations, the most important of which is the need to reconsider the privatization policies of agricultural development projects, because they did not achieve the desired results, and to rehabilitate these projects to play their previous role in developing the region and achieving economic and social stability for the citizens of the region.
Keywords: Economic Development; planning developmental; Rural communities; Rural development; Social development; Sudan